AFLP and SCAR markers associated with the sex in Gracilaria lemaneiformis (Rhodophyta). Issue 4 (17th June 2013) - Huan, Li; He, Linwen; Zhang, Baoyu; Niu, Jianfeng; Lin, Apeng; Wang, Guangce; Cock, M.
<x xml:space="preserve">Abstract</x> Gracilaria lemaneiformis (Bory de Saint‐Vincent) Greville, an important marine alga, has great economic and nutritional value. However, during the nonreproductive period, it is difficult to distinguish the sporophyte, male gametophyte, and female gametophyte from each other by appearance. Amplified fragment length polymorphism (AFLP) is a multilocus marker technique, which was used in this study to identify markers associated with G. lemaneiformis sex type. By applying 80 primer combinations in the screening process, three fragments were found that were specific to male or female forms of the alga. A 173 bp band and an 89 bp band were found in the sporophyte and the male gametophyte by using primer E‐AGG/M‐CGT. E‐ACC/M‐CGG was used to amplify a 118 bp specific fragment in the sporophyte and the female gametophyte. Sequence characterized amplified region (SCAR) primers were designed and showed the expected bands at the corresponding stages. This suggested that the SCAR markers that had been developed were successful. The joint use of the three primer pairs allowed us to characterize sex and the G. lemaneiformis developmental phase in the nondescript stages. Rapid gender testing is expected to improve cross‐breeding experiments and other genetic research in this economically important seaweed.